2006
DOI: 10.1111/j.0105-2896.2006.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3 ensembles in T‐cell regulation

Abstract: Our recent studies have identified dynamic protein ensembles containing forkhead box protein 3 (FOXP3) that provide insight into the molecular complexity of suppressor T-cell activities, and it is our goal to determine how these ensembles regulate FOXP3's transcriptional activity in vivo. In this review, we summarize our current understanding of how FOXP3 expression is induced and how FOXP3 functions in vivo as a transcriptional regulator by assembling a multisubunit complex involved in histone modification as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 155 publications
(204 reference statements)
0
61
0
Order By: Relevance
“…We previously found that FOXP3 existed as a large complex independent of FOXP3 oligomerization (11), which led us to explore the possible role of FOXP3 as a positive transcriptional repressor. The repressor function is clearly further developed by recruitment of transcription corepressors such as HAT and HDAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found that FOXP3 existed as a large complex independent of FOXP3 oligomerization (11), which led us to explore the possible role of FOXP3 as a positive transcriptional repressor. The repressor function is clearly further developed by recruitment of transcription corepressors such as HAT and HDAC.…”
Section: Discussionmentioning
confidence: 99%
“…FOXP3 may, for example, function as a passive transcriptional repressor in the case of its association with NFAT and NF-B (8,9). In this study, we explore the role of FOXP3 as an active transcriptional repressor by revealing the dynamic FOXP3 ensemble formation with a specific histone acetyltransferase (HAT) and certain class II histone deacetylases (HDACs) in expanded human CD4 ϩ CD25 ϩ regulatory T cells (10,11).…”
mentioning
confidence: 99%
“…31,53-60 FOXP3 forms part of a large protein complex that regulates the expression of hallmark genes associated with Treg cell phenotype. [61][62][63][64] The genomic region of the Foxp3 locus has several conserved non-coding sequences (CNS1, CNS2 and CNS3) that play different roles in the regulation of Foxp3 transcription. CNS1 contains binding sites for NFAT and AP-1 and is essential for peripheral, but not thymic, induction of FOXP3 expression.…”
Section: Mechanisms Underlying the Suppressive Function Of Foxp3 1 Trmentioning
confidence: 99%
“…Activated T CD4+CD25 low cells are probably the source of IL-2 in peripheral tissues in vivo (18). Antagonizing of Treg function could be obtained by signalling through GITR on the surface of effector T cells which is mediated by GITR ligand (GITR-L) on DCs' surface, or alternatively by secretion of IL-6 produced by activated DCs (19,20). Treg cells produce soluble GITR (sGITR) molecules which could interfere with GITR-L on DCs and block GITR/GITR-L interactions thus providing enhancement of suppression by Tregs (21).…”
Section: Phenotype and Function Of Natural Tregsmentioning
confidence: 99%